Nucleophosmin Protein Dephosphorylation by DUSP3 Is a Fine-Tuning Regulator of p53 Signaling to Maintain Genomic Stability - Russo, Lilian C.; Ferruzo, Pault Y. M.; Forti, Fabio L. (Frontiers in Cell and Developmental Biology, 2021)
The dual-specificity phosphatase 3 (DUSP3), an atypical protein tyrosine phosphatase (PTP), regulates cell cycle checkpoints and DNA repair pathways under conditions of genotoxic stress. DUSP3 interacts with the nucleophosmin protein (NPM) in the cell nucleus after UV-radiation, implying a potential role for this interaction in mechanisms of genomic stability. Here we show a high-affinity binding between DUSP3-NPM and NPM tyrosine phosphorylation after UV stress, which is increased in DUSP3 knockdown cells. Specific antibodies designed to the four phosphorylated NPM’s tyrosines revealed that DUSP3 dephosphorylates Y29, Y67, and Y271 after UV-radiation. DUSP3 knockdown causes early nucleolus exit of NPM and ARF proteins allowing them to disrupt the HDM2-p53 interaction in the nucleoplasm after UV-stress. The anticipated p53 release from proteasome degradation, increased p53-Ser15 phosphorylation, prolonged p53 half-life, and enhanced p53 transcriptional activity. The regular dephosphorylation of NPM’s tyrosines by DUSP3 balances the p53 functioning and favors the repair of UV-promoted DNA lesions needed for the maintenance of genomic stability.